Empowering learning strategies through study skills’ module - Zahari, Shafiyyah Solehah; Mohd Shaharuddin, Norfazlina; Teruk, Kamaril Azlah; Mohd Nasohah, Nor Sa'adah (Universiti Sains Islam Malaysia (USIM), 2024)
Foundation students having difficulties adapting to different learning styles in CFSIIUM as compared to secondary school. Therefore, the module of study skills was developed. Objective of this module is to guide the new students on the learning strategies in CFSIIUM. The module comprises of two components: learning strategies and discussion. The module was conducted in form of forum, where the facilitators shared their knowledge and experience, followed by the discussion. Online questionnaires on students'perception of the "Study Skills Module" were distributed among the foundation students. The module successfully met the expectations of the foundation students where the learning strategies shared by the facilitators was useful and can be applied by the foundation students. It is hoped that the foundation students will continue to excel in their academic performance. The module has a commercial potential as it is useful as a guidance for new students to gain new learning strategies and can be applied at school or other foundation programmes.